2019
DOI: 10.1017/s0967199419000479
|View full text |Cite
|
Sign up to set email alerts
|

Effects of melatonin on production of reactive oxygen species and developmental competence of bovine oocytes exposed to heat shock and oxidative stress during in vitro maturation CORRIGENDUM

Abstract: Zygote cambridge.org/zyg Corrigendum Cite this article: Cavallari F et al. (2019) Effects of melatonin on production of reactive oxygen species and developmental competence of bovine oocytes exposed to heat shock and oxidative stress during in vitro maturation CORRIGENDUM. Zygote 27: 262.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
2
0
1

Year Published

2022
2022
2022
2022

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 1 publication
0
2
0
1
Order By: Relevance
“…O melhoramento genético, com a introdução de genes termotolerantes, é uma possibilidade que deve ser estudada mais a fundo (31) . Além disso, outra opção seria o uso de substâncias antioxidantes na alimentação animal (31) ou sua adição no ambiente in vitro, uma vez que o estresse térmico gera produção excessiva de espécies reativas de oxigênio (ROS's), comprometendo a função do oócito (51) .…”
Section: Discussionunclassified
“…O melhoramento genético, com a introdução de genes termotolerantes, é uma possibilidade que deve ser estudada mais a fundo (31) . Além disso, outra opção seria o uso de substâncias antioxidantes na alimentação animal (31) ou sua adição no ambiente in vitro, uma vez que o estresse térmico gera produção excessiva de espécies reativas de oxigênio (ROS's), comprometendo a função do oócito (51) .…”
Section: Discussionunclassified
“…Genetic improvement, with the introduction of thermotolerant genes, is a possibility that should be studied further (31) . In addition, another option would be the use of antioxidant substances in animal feed (31) or their addition in the in vitro environment, since heat stress generates excessive production of reactive oxygen species (ROS's), compromising the function of the oocyte (51) .…”
Section: Discussionmentioning
confidence: 99%
“…Studies have reported that MLT can reduce ROS production during IVM in bovine (CAVALLARI et al, 2019;RODRIGUES-CUNHA et al, 2016) and some of them at the same concentration used in this experiment (10 -9 M) YANG et al, 2017;. When we used a combination of other two antioxidants (MQ+MT) they were able to decrease de ROS production relative to MLT, but not to control.…”
Section: Discussionmentioning
confidence: 62%